Transcriptomic responses of oil palm (Elaeis guineensis) stem to waterlogging at plantation in relation to precipitation seasonality - Lim, Hui; Kobayashi, Masaki J.; Marsoem, Sri Nugroho; Irawati, Denny; Kosugi, Akihiko; Kondo, Toshiaki; Tani, Naoki (Frontiers in Plant Science, 2023)
Global warming-induced climate change causes significant agricultural problems by increasing the incidence of drought and flooding events. Waterlogging is an inevitable consequence of these changes but its effects on oil palms have received little attention and are poorly understood. Recent waterlogging studies have focused on oil palm seedlings, with particular emphasis on phenology. However, the transcriptomic waterlogging response of mature oil palms remains elusive in real environments. We therefore investigated transcriptomic changes over time in adult oil palms at plantations over a two-year period with pronounced seasonal variation in precipitation. A significant transcriptional waterlogging response was observed in the oil palm stem core but not in leaf samples when gene expression was correlated with cumulative precipitation over two-day periods. Pathways and processes upregulated or enriched in the stem core response included hypoxia, ethylene signaling, and carbon metabolism. Post-waterlogging recovery in oil palms was found to be associated with responses to heat stress and carotenoid biosynthesis. Nineteen transcription factors (TFs) potentially involved in the waterlogging response of mature oil palms were also identified. These data provide new insights into the transcriptomic responses of planted oil palms to waterlogging and offer valuable guidance on the sensitivity of oil palm plantations to future climate changes.